Representasi Budaya Patriarki Dalam Drama “Higanbana: Keishichou No Sousa Nanaka” (Taro Otani, 2016) - Nadia Kembang Seranting; Asep Achmad Muhlisian (Janaru Saja Jurnal Program Studi Sastra Jepang, 2023)
Patriarchy is a social system that places men the main power holders. The purpose of this research is to represent patriarchal culture in the drama “higanbana: keishichou no sousa nanaka”. This research is a qualitative descriptive research using data analysis study techniques. The data analysis method using Roland Barthes theory of semiotics with the data source is drama “higanbana: keisichou no sousa nanaka”. The result of the analysis show that in the drama “higanbana: keishichou no sousa nanaka” in the dialogue and scenes it is seen that women are constructed to become human number two. This is illustrated by some coversations that suggest men have a control over woman. Patriarchal representation appears in four areas, namely, women’s productive power & labor, women’s reproduction, control ever women’s sexuality and women’s movement/mobility. Women are not given the freedom and the right to choose as they wish. Keywords: representation, patriarchy, Roland Barthes’ semiotics